2023
DOI: 10.35741/issn.0258-2724.58.3.35
|View full text |Cite
|
Sign up to set email alerts
|

Investment Behaviour of Individual Investors Regarding Sharia Stock Investment: A Systematic Review

Abstract: The main purpose of this paper is to review existing relevant pieces of literature on the behavior of investors toward investment in sharia stocks and bring into focus the factors that affect investors' behavior in investment decision-making regarding sharia stocks. The paper is descriptive and exploratory and based on secondary data sourced from trusted e-journals, research databases, and e-magazines. The factors that influence investment decisions can be complex and may vary from one individual to another. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Correspondingly, H2 was supported. In this respect, Hussain et al (2023) reported that an individual's knowledge of Islamic Sukuk positively influenced their intention to invest in such an investment. In addition, according to Duqi and Al-Tamimi (2019), the most critical issues for investors are connected to the availability of information and a broad understanding of Sukuk issuances in terms of credit, market and liquidity risk.…”
Section: Testing the Research Hypotheses And Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Correspondingly, H2 was supported. In this respect, Hussain et al (2023) reported that an individual's knowledge of Islamic Sukuk positively influenced their intention to invest in such an investment. In addition, according to Duqi and Al-Tamimi (2019), the most critical issues for investors are connected to the availability of information and a broad understanding of Sukuk issuances in terms of credit, market and liquidity risk.…”
Section: Testing the Research Hypotheses And Discussionmentioning
confidence: 99%
“…Similarly, Faisal et al (2023) argued that the decision to invest in Sukuk is heavily impacted by social factors. In the same way, Hussain et al (2023), who investigated the factors that influence individuals' decisions to invest in Islamic sukuk, revealed that social factors played a vital role in motivating people to invest their money in Islamic Sukuk. Besides, by understanding and leveraging the power of social influence, organizations and institutions can effectively encourage and promote investments in Hajj funds, facilitating the fulfillment of religious obligations and fostering a sense of communal support within the Muslim community.…”
Section: Literaturementioning
confidence: 99%
“…Valencia et al, (2022), evaluating the regulatory frameworks implemented by various jurisdictions during 2020-2023 will contribute to understanding the index's conditions; (3) Islamic Finance Governance, the governance of Islamic finance institutions and regulatory bodies impacts investor confidence and the overall growth of Shariah-compliant investments (Hasan et al, 2020). Examining the initiatives taken in this regard will provide a holistic view of the index's development; (4) Industry Growth and Investment Trends, tracking the growth of the Islamic finance industry and the corresponding investment trends will shed light on the market sentiment surrounding Shariah-compliant assets (S. Aziz et al, 2022;Touti & Taïb, 2023); (5) Investor Sentiment and Risk Appetite, analyzing investor sentiment and risk appetite towards Shariah-compliant assets during the specified period will provide insights into the index's performance (Anwer, 2021;Hussain et al, 2023). Factors such as geopolitical events, market volatilities, and investor preferences influence the overall sentiment (Hachicha, 2023;He, 2023).…”
Section: Discussionmentioning
confidence: 99%